The Development of Problem-Solving Process Skills in Chemistry On Topic of Chemistry and Problem-Solving Using Project-Based Learning for Grade 12 Students at Yangtalatwittayakarn School - ศิริธรรมจักร สิริพรรณ; Boonnan, Bussawan; สร้อยกุดเรือ นัฏฐารุจา; Leamsamrong, Kwanyuen (Journal for Developing the Social and Community, 2025)
Background and Aims: This research aims to develop problem-solving process skills in chemistry on the topic of "Chemistry and Problem-Solving" through Project-Based Learning (PBL) for Grade 12 students at Yang Talat Wittayakarn School. The objectives of this study were: (1) to compare students’ process skills after participating in project-based learning activities in the "Chemistry and Problem-Solving" topic, ensuring effectiveness based on the 70/70 criterion; (2) to compare students’ learning achievement after instruction against the 70/70 criterion; and (3) to examine students’ satisfaction with project-based learning. Methodology: The target group consisted of 35 Grade 12 students in the science-mathematics program at Yang Talat Wittayakarn School, enrolled in the second semester of the 2024 academic year. The research instruments included (1) six lesson plans, (2) a 20-item multiple-choice achievement test with item difficulty ranging from 0.20 to 0.77 and discrimination indices from 0.60 to 1.00, and (3) a 10-item satisfaction questionnaire. Percentage, Mean, Standard Deviation, Content Validity, Difficulty, Discrimination and Reliability. Results: The research findings revealed that: (1) in the first action cycle, students’ average achievement score was 14.91 points (74.57%). In the second action cycle, after implementing lesson plans 3-4, the average score increased to 16.37 points (81.86%). In the third action cycle, after implementing lesson plans 5-6, the average score further increased to 17.97 points (89.86%); (2) when compared to the set criteria, lesson plans 1-2 met the 70% threshold, but five students did not pass. Conclusion: These students were provided with additional worksheets and remedial instruction. Similarly, in the second cycle, lesson plans 3-4 met the criteria, but three students required additional support. In the third cycle, lesson plans 5-6 successfully met the criteria, and students’ post-test scores showed a statistically significant improvement at the 0.05 level; and (3) students’ satisfaction with project-based learning was rated as very high ( = 4.52, S.D. = 0.52). Background and Aims: This research aims to develop problem-solving process skills in chemistry on the topic of "Chemistry and Problem-Solving" through Project-Based Learning (PBL) for Grade 12 students at Yang Talat Wittayakarn School. The objectives of this study were: (1) to compare students’ process skills after participating in project-based learning activities in the "Chemistry and Problem-Solving" topic, ensuring effectiveness based on the 70/70 criterion; (2) to compare students’ learning achievement after instruction against the 70/70 criterion; and (3) to examine students’ satisfaction with project-based learning. Methodology: The target group consisted of 35 Grade 12 students in the science-mathematics program at Yang Talat Wittayakarn School, enrolled in the second semester of the 2024 academic year. The research instruments included (1) six lesson plans, (2) a 20-item multiple-choice achievement test with item difficulty ranging from 0.20 to 0.77 and discrimination indices from 0.60 to 1.00, and (3) a 10-item satisfaction questionnaire. Percentage, Mean, Standard Deviation, Content Validity, Difficulty, Discrimination and Reliability. Results: The research findings revealed that: (1) in the first action cycle, students’ average achievement score was 14.91 points (74.57%). In the second action cycle, after implementing lesson plans 3-4, the average score increased to 16.37 points (81.86%). In the third action cycle, after implementing lesson plans 5-6, the average score further increased to 17.97 points (89.86%); (2) when compared to the set criteria, lesson plans 1-2 met the 70% threshold, but five students did not pass. Conclusion: These students were provided with additional worksheets and remedial instruction. Similarly, in the second cycle, lesson plans 3-4 met the criteria, but three students required additional support. In the third cycle, lesson plans 5-6 successfully met the criteria, and students’ post-test scores showed a statistically significant improvement at the 0.05 level; and (3) students’ satisfaction with project-based learning was rated as very high ( = 4.52, S.D. = 0.52).